Evaluating the Effects of Wheat Cultivar and Extrusion Processing on Nutritional, Health-Promoting, and Antioxidant Properties of Flour - Bangar, Sneh Punia; Sandhu, Kawaljit Singh; Rusu, Alexandru; Trif, Monica; Purewal, Sukhvinder Singh (Frontiers in Nutrition, 2022)
Wheat has been considered one of the most important staple foods for thousands of years. It is one of the largest suppliers of calories in the daily diet, which is added to many different products. Wheat is also a good source of health-benefiting antioxidants. This study aims toinvestigate the changes in the antioxidant properties, such as total phenol content, 2,2-diphenyl-1-picrylhydrazyl (DPPH), metal chelating activity, 2,2′-azino-bis (3-ethylbenz-thiazoline-6-sulfonic acid) diammonium salt (ABTS+) scavenging activity, and color intensity, during the extrusion processing of six different wheat cultivars. The extrusion factors evaluated were 15% feed moisture and two extrusion temperatures (150 and 180°C). Extrusion processing increased antioxidant activity (DPPH, metal chelating activity, and ABTS+ scavenging activity), whereas total flavonoids content and total phenolic content were decreased. The L* values of wheat flours increased significantly (p < 0.05) after extrusion at 150 and 180°C, 15% mc. Furthermore, redness was decreased from control wheat cultivars (range: 0.17–0.21) to extrusion at 150°C (range: 0.14–0.17) and 180°C (range: 0.1–0.14). The study suggests that extruded wheat could improve the antioxidant potential in food products.